A domain of influence theorem in linear thermo-elasticity with thermal relaxation and internal variable - Cimmelli, V.A.; Rogolino, P. (Archives of Mechanics, 2002)
A domain of influence theorem is proved for a linear thermoelastic solid with a Cattaneo’s type heat conduction law and a scalar internal variable. The obtained result is applied to prove the hyperbolicity of a semiempirical heat conduction theory, describing the propagation of thermal waves in crystals at low temperatures.